The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/1469-7610.00234
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity, parental vulnerability and disorder: examining inter‐generational transmission of risk

Abstract: Background: An investigation of intergenerational factors associated with psychiatric disorder in late adolescence/early adulthood was undertaken to differentiate influences from maternal disorder, maternal poor psychosocial functioning and poor parenting, on offspring. Method: The sample comprised an intensively studied series of 276 mother-offspring pairs in a relatively deprived inner-city London area with high rates of lone parenthood and socio-economic disadvantage. The paired sample was collected over tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 36 publications
11
120
1
3
Order By: Relevance
“…A large body of research indices that the optimum behavior of the children depend upon the parenting style (Barbara, 2004) and (Brink , 2006). Numerous research has documented the inter-generational continuity of parenting indicative of that present day parent tend to use similar parenting strategies or practices that they themselves received in their child hood (Bifulco, et al, 2002) .Children behavior are action in response to many internal and external influences (Osborne & Fincham, 1996). Possible internal influences of behavior are genes; metabolism, age and gender while external influences of behavior are parental behavior and peer models (Hops, Davis, Leve, & Sheebe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research indices that the optimum behavior of the children depend upon the parenting style (Barbara, 2004) and (Brink , 2006). Numerous research has documented the inter-generational continuity of parenting indicative of that present day parent tend to use similar parenting strategies or practices that they themselves received in their child hood (Bifulco, et al, 2002) .Children behavior are action in response to many internal and external influences (Osborne & Fincham, 1996). Possible internal influences of behavior are genes; metabolism, age and gender while external influences of behavior are parental behavior and peer models (Hops, Davis, Leve, & Sheebe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Confusion with the aggressor was revived again by the sight of the baby's penis, as with her first baby. She was reactivating a fundamental violence (Bergeret, 1984) that could not be supported by any libidinal basis; it sent her back to her own childhood history with her parents: "It was a boy. He was naked, even uglier than the first one and with an enormous thing .…”
Section: Transmission Of Abuse-related Sequellae and Investment In Chmentioning
confidence: 99%
“…Most clinical studies have arrived at the same conclusions, including the high frequency of greater psychiatric perturbations among adults abused during early development (Bifulco et al, 2002;Lueger-Schuster et al 2014, Lynskey & Fergusson, 1997McCloskey, 2013;Polusny & Follette, 1995). The perturbations show up as a greater number of anxiety, depressive, and personality disorders; risk of psychosis; substance use; and post-traumatic stress disorders (PTSD), among other problems.…”
mentioning
confidence: 96%
“…There is evidence that parenting behaviors mediate the association between maternal depression and adverse child outcomes such as child social competence and child psychopathology (Goodman & Brumley, 1990;Bifulco, Moran, & Ball, 2002;Coyl et al, 2002). Specifically, Coyl and colleagues (2002) found that maternal depression predicted negative mother-child interactions and frequency of spanking, which in turn predicted poor infant attachment security.…”
Section: Parenting Behaviors During Mother-offspring Interactions As mentioning
confidence: 99%
“…There is growing evidence that suboptimal parenting behaviors, specifically parenting behaviors that occur during mother-infant interactions, mediate the negative impact of maternal depression on offspring behavior outcomes (Goodman & Brumley, 1990;Bifulco et al, 2002;Coyl et al, 2002). Given the mediating role of parenting behaviors between maternal depression and offspring negative outcomes, intervening to improve parenting behaviors among depressed mothers represents a potentially promising route to reduce the risk of negative offspring outcomes.…”
Section: Future Directionsmentioning
confidence: 99%